SIMULATION OF CO DISTRIBUTION FROM TEXTILE INDUSTRY COAL FUEL AND CO RELATIONSHIP TOWARDS PNEUMONIA SUFFERERS AT CIMAHI REGION - HANIFAH (NIM: 12814016), NURUL
This research was conducted to know the dispersion of CO from boiler chimney of textile factory and its relationship towards toddlerÃ‚Â’s pneumonia. The dispersion of CO with CALPUFF model which is a non-steady distribution model that simulates spatial distribution patterns by considering meteorological conditions such as wind, atmospheric stability as well as complex land effects to know how far the distribution of pollutant. Relationship of CO to pneumonia disease is analyzed by looking at the comparison from the observation and position of Public Health Center to influential meteorological conditions. The observation results at May 8th2018 indicated that wind, temperature, and humidity influenced the dispersion of CO. The influence is not significant at point 0 m and 500 m observation, but it has influence at point 1 km on 7 a.m. The highest sufferer of pneumonia was located at Cigugur Tengah Public Health Center (38.09%) when CO spread to the north east part of the factory. The highest sufferer of pneumonia was found at Pasir Kaliki Public Health Center (23.8%) when CO spread to the south part of the factory. Symptoms of pneumonia in toddler such as cough, difficulty breathing, and rapid breathing on the toddler most often occur in the morning and evening. Simulation indicated that pollution spread to the direction of south-east and north-west. The highest CO concentration spread was 10-6 mg/m3.